Coding guidelines. - Green, Robert; Ledgard, Henry (Communications of the ACM, 2011)
The article discusses coding, providing a system of coding guidelines which can be applied to make code more maintainable, clear, and understandable. The article looks at the use of the fixed-width fonts, vertical alignment, and names based on simple English as well as white space and context to make code more readable and understandable. The article also suggests that the structure of code rather than the syntax of the programming language should drive layout. The author say that these guidelines could be used in both education and industry.